Perlindungan Hukum Bagi Hak-Hak Pekerja Terhadap Kasus Pemutusan Hubungan Kerja (PHK) Secara Sepihak Ditinjau Dari Undang-Undang Nomor. 6 Tahun 2023 Tentang Cipta Kerja - Imam Mutakin; Usep Saepuloh; Naya Dewi Elvina; Tita Wulan Dini; Ahmad Fajar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Basically, Termination of Employment (PHK) is an action that must be avoided and must not be allowed to occur. However, the problem of layoffs in a company at this time often occurs. Termination of employment is the termination of a person as an employee accompanied by the provision of financial compensation by the company where he works. Termination of Employment (PHK) can occur at any time, but of course it must not be done unilaterally by the company, because this will be detrimental to workers/laborers. Legal protection against unilateral termination of employment (PHK) has been regulated in Article 153 of the Job Creation Law, where in Termination of Employment (PHK) employers are prohibited from carrying out unilateral Termination of Employment (PHK), except in certain circumstances that force PHK to be carried out, as stipulated in Law Number 6 of 2023. Unilateral layoffs carried out by companies not only violate the Employment Laws and This research uses a normative juridical legal research method with a statute approach and a conceptual approach. The results of this study indicate that termination of employment (PHK) has a legal basis, as stipulated in Article 151 of the Job Creation Law, which discusses the procedures for terminating employment (PHK).